2001
DOI: 10.1063/1.1367275
|View full text |Cite
|
Sign up to set email alerts
|

Electron affinity of AlxGa1−xN(0001) surfaces

Abstract: The electronic properties and the electron affinities of AlxGa1−xN(0001) surfaces were investigated by ultraviolet photoemission spectroscopy (UPS) over the whole composition range. The samples were prepared by N-ion sputtering and annealing. Surface cleanliness and stoichiometry were monitored with x-ray photoemission spectroscopy. Samples with high aluminum content showed traces of oxygen which could not be removed by further cleaning cycles. However, we have evidence that the oxygen is located in the bulk a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
95
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(110 citation statements)
references
References 21 publications
13
95
1
1
Order By: Relevance
“…[94][95][96][97][98][99] The calculated electron affinity for AlN is 1.01 eV for relaxed surfaces (0.52 eV for unrelaxed), which is again within the range of reported experimental values [0.25 ± 0.3 eV, 100 1.9 eV, 101 and 0 eV (Ref. 99)].…”
Section: Electron Affinities and Ionization Potentials Of Binary Nitrsupporting
confidence: 65%
“…[94][95][96][97][98][99] The calculated electron affinity for AlN is 1.01 eV for relaxed surfaces (0.52 eV for unrelaxed), which is again within the range of reported experimental values [0.25 ± 0.3 eV, 100 1.9 eV, 101 and 0 eV (Ref. 99)].…”
Section: Electron Affinities and Ionization Potentials Of Binary Nitrsupporting
confidence: 65%
“…23 According to the Schottky-Mott (SM) theory, the SBH at the interface between graphene and AlGaN is given by φ b = φ G − χ s , where φ G = 4.5 eV is the graphene work function, 24 and χ s is the electron affinity of Al x Ga 1−x N. Since χ s decreases as x increases, the SBH also increases with x. Grabowski et al reported the electron affinities of GaN and AlN as 3.1 eV and 0.25 eV, respectively. 25 On the other hand, some other studies reported that the electron affinities of GaN and AlN are 4.2 eV and 2.05 eV, respectively. 23,26 Therefore, the calculated SBH value is dependent on the value of Al x Ga 1−x N electron affinity used in the calculation.…”
Section: Methodsmentioning
confidence: 99%
“…However, for an efficient implementation, it is convenient to assume that the screened pseudopotentials are well represented by their is set to the work function, which can be obtained from experimental data 14 or obtained from ab initio calculations. In nanostructures, as superlattices or quantum wells, v + (G = 0) determines the band alignment and its value has to be set carefully.…”
Section: Construction Of Semiempirical Pseudopotentials From Bulkmentioning
confidence: 99%